Transmitting the spirit : religious conversion, media, and urban violence in Brazil - Oosterbaan, Martijn, 1975- (University Park, Pennsylvania : The Pennsylvania State University Press, 2017)
"Examines Pentecostalism, media, society, and culture in the turbulent favelas of Brazil. Explores both the evolving role of religion in Latin America and the proliferation of religious ideas and practices in the postmodern world"--Provided by publisher.
The Manichean city : socio-spatial segregation and Pentecostalism -- Sonic struggles : sound, religion, and space in the favelas -- Mass mediating spiritual battles : Pentecostalism and the daily news -- "Deliver this favela" : space, violence, and hypermediated conversion -- Spiritual attunement : Pentecostalism and listening -- "Written by the devil" : suspicious television.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Pentecostalism -- Brazil; Mass media -- Brazil; Mass media -- Religious aspects -- Pentecostal churches; Conversion -- Pentecostal churces; Slums -- Brazil -- Rio de Janeiro; Urban violence -- Brazil; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books